OP0060 Health behavior in adolescents with juvenile idiopathic arthritis- results of the inception cohort of newly diagnosed patients (ICON). (15th June 2017) - Listing, M; Liedmann, I; Niewerth, M; Klotsche, J; Mönkemöller, K; Foeldvari, I; Kümmerle-Deschner, J; Hospach, T; Minden, K
Abstract : Background: Knowledge concerning health behavior in adolescents with juvenile idiopathic arthritis (JIA) is essential for assessing their health risks. Although there is some evidence about a relationship between low socioeconomic status (SES) and health risk behavior in adulthood, it is less clear whether this association is also true for adolescents with JIA. Objectives: To compare the health behavior between adolescents with JIA and healthy peers and to examine the association with sex and SES. Methods: Data of adolescents (aged 13 to 17) with JIA and healthy peers enrolled in ICON were considered for this analysis. Health behavior was assessed via questionnaire within the first years of disease. SES- Score (low, moderate, high) was determined by using an established German multidimensional aggregated index and based on the parents' education level as well as household net income. Results: A total of 334 adolescents with JIA (61% female, mean age 15.1 (SD 1.1), mean disease duration 1.3 (SD 1.7)) and 181 healthy peers (57% female, mean age 15.3 (SD 1.3)) were included. Adolescents with JIA were less physically active and reported less consumption of alcohol compared with healthy peers (see Table). In both groups, boys were more frequently physically active and spent more time in playing video games than girls. Whereas girls with and without JIA used more often mobile phones than boys. No gender specific differences in both groups were found in consumption of illicit and legal drugs. After stratification in groups according to the SES- Scores, socioeconomic differences were the same in adolescents with JIA and healthy peers. Teenagers with low social background (n=200) spent significantly more time in consumption of TV, mobile phones and video games than those from families with high SES (n=122). No significant relationship was found between parental SES and alcohol, nicotine and drug consumption by adolescents. The parental SES- Score was strongly associated with the education level of adolescents. Conclusions: Adolescents with JIA have a similar health behavior as healthy peers, except for alcohol consumption and physical activity level. Gender and socioeconomic status are associated with health behavior of adolescents with and without JIA. Parental SES may affect adolescents' educational outcomes. Acknowledgements: ICON is supported by a grant from the Federal Ministry of Education and Research (FKZ: 01ER0812). Disclosure of Interest: M. Listing: None declared, I. Liedmann: None declared, M. Niewerth: None declared, J. Klotsche: None declared, K. Mönkemöller: None declared, I. Foeldvari: None declared, J. Kümmerle-Deschner: None declared, T. Hospach: None declared, K. Minden Speakers bureau: Pfizer, Roche, Pharm-Allergan